Seabird abundance, biomass and prey consumption within Prydz Bay, Antarctica, 1980/1981–1992/1993: - Woehler, Eric J. (Polar Biology, 1997)
Annual observations of seabirds within Prydz Bay, East Antarctica, between the 1980/1981 and 1992/1993 seasons revealed siginificant changes in abundance of the 9 resident and 15 non-resident species. An estimated 4.85 million individual residents and 2.35 million individual non-residents were present each season. For resident and non-resident species, mean abundance was 3.75 and 1.81 birds/km2, and mean biomass was 6.67 and 1.70 kg/km2, respectively. Based on estimated abundances, the total consumption of marine resources by the seabird community within Prydz Bay ranged from 471,000 to 1.1 million tonnes (mean 752,000±176,000 tonnes) per 6-month summer, or between 2.02 and 4.53 kg/km2 per day (mean 3.23±0.76 kg/km2 per day). The mean energy flux to the seabird community within Prydz Bay each summer was 3.13*1012 kJ, (range: 2.0*1012 kJ–4.4*1012 kJ), of which 66% went to the resident species. Regional abundance and biomass estimates for resident and non-resident species were both negatively correlated; when the estimated abundance and biomass of resident species were high, those of non-resident species were low.